Co-creating public value into digital-based public service innovation in the village governance - Hajar, Siti; Arma, Nur Ambia (Otoritas : Jurnal Ilmu Pemerintahan, 2024)
Digital technology is a solution in improving public services and governance, such as in administrative services with open access information. In organizing public services, the Hamparan Perak village government uses web-based applications, which aim to prevent corruption, increase transparency and reduce administrative costs in governance. This research uses a survey method, and is processed through smart PLS software. The results of this study indicate that digital-based public service innovation has a t value of 138.059 and a p value of 0.000. In addition, the results show that digital-based public service innovation has a significant positive effect on public value creation, which is 1.96. Thus, by implementing an electronic system in governance, Hamparan Perak Village can co-create public value by fulfilling the strategic trangle and relating to the main components that can differentiate services provided by public and private organizations. The form of innovation in optimizing digital-based public services in Hamparan Perak Village is the application of web applications. This will strengthen the co-creation of public value derived from the level of community satisfaction through community trust and support for the implementation of web-based governance in Hamparan Perak Village.